Hubungan antara Basic PSychological Need dengan Pengabilan Keputusan Karir pada Siswa Kelas XI Jurusan Akuntansi SMK 11 Bandung - aulia trisdaloka; Endang Supraptiningsih (Bandung Conference Series: Psychology Science, 2023)
Abstract. Career decision making has an impact on human life, including adolescents. Career decision making in adolescents is influenced by internal and external factors. One of the internal factors in making career decisions is self-determination on aspects of basic psychological need. The phenomenon of class XI students majoring in accounting at SMK 11 Bandung shows that most students have not been able to make a decision because parents are still very instrumental in making their career decisions, where this affects the learning process of students at school even in the career plans that will be chosen. The purpose of this study was to determine the close relationship between Basic Psychological Need and Career Decision Making in class XI students majoring in Accounting at SMK 11 Bandung. This study uses the theory of Basic Psychological Need from Ryan & Deci (2017) and the theory of career decision making from Parsons (in Super 2010). This research uses quantitative research methods with correlational research methods. This study involved 101 students majoring in accounting with data collection using a questionnaire. The results of data analysis using Spearman rank correlation test. The results of this study indicate that there is a relationship (correlation) between Basic Psychological Need and Career Decision Making in class XI students majoring in accounting at SMK 11 Bandung with a correlation value of 0.795. That is, the higher the basic psychological need, the higher the career decision making. Abstrak. Pengambilan keputusan karir memberikan pengaruh bagi kehidupan manusia termasuk pada remaja. Pengambilan keputusan karir pada remaja dipengaruhi oleh faktor internal dan ekternal. Salah satu fakor internal dalam pengambilan keputusan karir adalah self determination pada aspek basic psychological need. Fenomena pada siswa kelas XI jurusan akuntansi SMK 11 Bandung menunjukan bahwa kebanyakan siswa belum mampu dalam mengambil sebuah keputusan karena dalam orang tua masih sangat berperan dalam pengambilan keputusan karir mereka, dimana hal ini mempengaruhi proses pembelajaran siswa disekolah bahkan dalam rencana karir yang akan dipilih. Tujuan dari penelitian ini adalah untuk mengetahui keeratan hubungan antara Basic Psychological Need dengan Pengambilan Keputusan Karir pada siswa kelas XI jurusan Akuntansi SMK 11 Bandung. Pada penelitian ini menggunakan teori Basic Psychological Need dari Ryan & Deci (2017) dan teori pengambilan keputusan karir dari Parsons (dalam Super 2010). Penelitian ini menggunakan metode penelitian kuantitatif dengan metode penelitian korelasional. Penelitian ini melibatkan 101 siswa jurusan akuntansi dengan pengumpulan data menggunakan kuesioner. Hasil analisis data menggunakan uji korelasi rank spearman. Hasil penelitian ini menunjukan terdapat hubungan (korelasi) antara Basic Psychological Need dengan Pengambilan Keputusan Karir pada siswa kelas XI jurusan akuntansi SMK 11 Bandung dengan nilai korelasi sebesar 0,795. Artinya, semakin tinggi basic psychological need maka semakin tinggi pula pengambilan keputusan karir.